Radiography of the distal extremity of the manus in the donkey foal: Normal images and quantitative characterization from birth to 2 years of age: A pilot study. (6th December 2017) - Van Thielen, B.; Willekens, I.; Van der Schicht, A.; Pestieau, P.; Verhelle, F.; Goossens, P.; Decoster, R.; Jacqmot, O.; Delperdange, P.; Busoni, V.; De Mol, G.; Buls, N.; et al.
Summary: This study describes a radiographic survey of the anatomical development of the distal extremity of the manus in the donkey from 0 to 2 years of age. The right distal limb of 10 donkey foals, born in the spring of 2012, underwent radiographs every month for the first 6 months of age and every 3 months during the following 18 months. Latero‐medial radiographs with and without barium marker at the coronary band and dorso‐palmar radiographs with both front feet in weight bearing were obtained. The distal physis of the third metacarpal bone and the proximal physis of the proximal phalanx ( phalanx proximalis ) were closed at the mean age of 18.6 months. The distal physis of the proximal phalanx appeared as a clear radiolucent line at 2 weeks of age and was still subtly visible in some donkeys at 24 months. The proximal physis of the middle phalanx ( phalanx media ) was closed at the mean age of 16.7 months. The distal physis of this phalanx was visible at birth, but closed at 4 days. The distal phalanx (phalanx distalis) was triangular at birth. At the age of 20–21 months, the palmar processes (processus palmares) were both developed. The navicular bone (os sesamoideum distalis) was developed at the mean age of 9 months. The proximal sesamoid bones (ossa sesamoidea proximalia) were seen in continuously development during the 24 months. It seems that the physes in the distal extremity of the manus in the donkey close at an older age than the physes in the horse.